O discurso do idoso sobre a velhice - Falcão, Juliana de Souza (2008)
With the increase in the number of elderly in our society is important analyze and discuss this theme as this segment is a new and growing demand for various professions. Thus, to understand the process of aging in Brazilian society today allows us to move closer to this reality, identifying the real needs of this population. Thus, this study aims to analyze the speech of the elderly on the old age. To do so, we identify the heterogeneity that constitutes the speech of the elderly, as well as we investigate the speech over the life experience and the feelings relating to ageing. The data collection occurred in the Attention to the Elderly Program (PAI) in the General Hospital of Areias in the city of Recife with 15 participants who were part of an Workshop of Language. We use a qualitative methodology. Data analysis was based on the Analysis of Speech by Pêcheux, especially in the third period, taking into account both the proposals and the questions of his last period. In this sense, is based on the prospect of Teixeira (2005) concerning diversity and non-coincidences. In the speech of the elderly we identify the crossing of religious, aesthetic and medicinal speeches. Through their speeches, first identified a sense, superficial, which the participants feel and live to old age in a positive way. But that sense is destabilised by the first statement since those listed have proved contradictory, non-overlapping, creating new meanings.. We hope that the knowledge generated can become suport for the implementation of programs for the planning of care and intervention strategies appropriate to the reality, thus contributing to a process of ageing, but with a full life, which at least look at this direction